Integrating the issues of world animal health and world public health into the veterinary curriculum: a Southeast Asian perspective - Saad, Mohd Zamri; Sidik Budiono, Romziah; Kunavongkrit, Annop; Valdez, C. A.; Thien, M. (Office International des Epizooties, 2009)
The authors analysed the curricula of five veterinary schools in Southeast Asia to determine how successfully they integrate the issues of global animal health and global public health into their programmes. Two schools offer a five-year programme while the remaining three offer a six-year programme. The core courses within the curricula range from 145 to 224 credit hours, in total. In general, world animal health and world public health are well integrated into the veterinary curriculum. Most curricula allocate approximately 3% of their total credit hours to subjects associated with animal and public health, but other subjects that may contain discussions on these issues range between 6% and 10%. Most veterinary schools in Southeast Asia offer a Master's programme in Veterinary Public Health, with detailed emphasis on animal and public health but focusing principally on topics of local importance. At the same time, undergraduate and post-graduate veterinary students are exposed to current issues in animal and public health through regional and international scientific meetings.